ダイ35ジ ナンキョク チイキ カンソクタイ エットウタイ ホウコク 1994-1995 - 横山, 宏太郎; ヨコヤマ, コウタロウ; Yokoyama, Kotaro (1998)
P(論文) 第35次南極地域観測隊越冬隊は, 越冬隊長横山宏太郎以下40名で構成され, 1994年2月1日から1995年1月31日までのあいだ昭和基地の運営・維持管理を行うとともに, 計画に基づき昭和基地, 沿岸, 内陸で観測および設営活動を行った。同隊が南極に到着した1993-1994年の夏は, 厳しい海氷状況のため「しらせ」が昭和基地接岸を断念し, 物資輸送の遅れ, 夏の作業の遅れなどが起こり, また当初予定になかった秋の中継拠点旅行を実施することになり越冬中の観測, 作業にも大きな影響があった。それにもかかわらず, 越冬交代以後1年間, 観測, 設営活動を順調に実施し, ほぼ予定通りの成果を上げ全員元気に帰国した。昭和基地では第33次隊で建設を開始した管理棟の通信室や医務室の内部設備が完成し, 全面的な使用を開始した。またこれに接続する通路棟も部分的に建設され, 基地生活はより快適となった。これに加え, 設営では昭和基地の機能を維持・向上させるため, 火災報知器はじめ諸設備を点検整備し, 年間を通じて安定的に使用した。昭和基地における観測では, 過去最大規模のオゾンホール出現の観測, 大気微量成分の高精度観測, 超伝導重力計による常時地球自由振動の発見をはじめとして多くの成果を上げ, 貴重なデータを収集した。設営部門の積極的な支援を受け, 野外活動が盛んに行われた。沿岸地域では海氷圏の生物基礎生産過程の調査や地学調査を実施した。またやまと山脈では航空機を利用した調査により古地磁気学用サンプルを採取した。内陸では氷床ドーム深層掘削観測計画の第3年次にあたり, ドームふじに新しい観測拠点を建設し, 必要物資の輸送とあわせて第36次からのドームふじ越冬・掘削開始を可能とした。 The wintering party of the 35th Japanese Antarctic Research Expedition (JARE-35), which was consisted of 40 members, wintered at Syowa Station from February 1994 to January 1995. In the austral summer of 1993 to 1994,quite severe sea ice conditions forced the icebreaker SHIRASE to stop 20km from Syowa Station. The summer operations of transportation and construction were delayed and the wintering schedule had to be modified. However, the planned tasks were completed successfully. The main building of Syowa Station was completed after 3 years of construction improving living standards. The station facilities were maintained very well through the efforts of the logistic members. Observations at Syowa Station were conducted on various subjects such as meteorology, upper atmosphere physics and environmental sciences. The total ozone content reached a minimum value in October 1994. The incessant excitation of the Earth's free oscillations was confirmed by a superconducting gravimeter. Intensive field activities in geology, geomagnetism, marine biology and glaciology were carried out in the coastal areas, Yamato Mountains and inland plateau. The wintering period of JARE-35 was the 3rd year of the deep ice core drilling project at Dome Fuji Station. Several inland traverse ...